Antifungal Activity of Naphtoquinone From Tabebuia Serratifolia (Vahl. Nicholson) - Velásquez, J; Rojas, L.B; Usubillaga, A (Ciencia)
The presence of naphtoquinones has been reported in several species of Tabebuia. It is known that naphtoquinones are biologically active against pathogenic fungi. An ethanolic extract of the wood of Tabebuia serratifolia showed activity against the wood rotting fungi Gloeophyllum trabeum and Trametes versicolor. Chromatography of the ethanolic extract yielded lapachol, [2-hydroxy-3-(3-methyl-2-butenyl)-1,4 naphtoquinone], which was proved to be the active principle and its identity was established by comparison of its spectroscopic properties with published data. The antifungal activity of this naphtoquinone was investigated using the agar dilution method with superficial inoculation, at concentrations of 30, 40, 50, 60, and 70 µg/mL. Lapachol showed fungicidal activity against G. trabeum and T. versicolor at 60 µg/mL and fungistatic between 30 and 50 µg/mL. Correlation analysis showed that as much as 96% of the variation in growth inhibition could be accounted for increased lapachol concentration.